Modified e-slotted patch antenna for WLAN/Wi-Max satellite applications - Akanksha Gupta; D. K. Srivastava; J. P. Saini (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
A low profile modified e-slotted microstrip antenna is proposed for multiple wireless communication applications. The performance of antenna is measured in terms of return loss, current distribution. The effect of variation of height of substrate on antenna impedance bandwidth is also studied. The antenna with overall size 30×50×.8m.m.3 resonates at eight frequencies which covers some important applications like GPS, wireless local area network (WLAN), worldwide interoperability for microwave access (WiMax), Satellite communication etc. The proposed antenna structure offers great advantages due to compact size, simple structure and multiple applications. The multi band antenna was designed and optimized using ansoft HFSS v13 simulator. The simulated result is good agreement with measured result.